Immobilization of Pichia pastoris cells containing alcohol oxidase activity - Maleknia, S (Tehran University of Medical Sciences, 2011)
BACKGROUND AND OBJECTIVES: The attempts were made to describe the development of a whole cell immobilization of P. pastoris by entrapping the cells in polyacrylamide gel beads. The alcohol oxidase activity of the whole cell Pichia pastoris was evaluated in comparison with yeast biomass production. MATERIALS AND METHODS: Methylotrophic yeast P. pastoris was obtained from Collection of Standard Microorganisms, Department of Bacterial Vaccines, Pasteur Institute of Iran (CSMPI). Stock culture was maintained on YPD agar plates. Alcohol oxidase was strongly induced by addition of 0.5% methanol as the carbon source. The cells were harvested by centrifugation then permeabilized. Finally the cells were immobilized in polyacrylamide gel beads. The activity of alcohol oxidase was determined by method of Tane et al. RESULTS: At the end of the logarithmic phase of cell culture, the alcohol oxidase activity of the whole cell P. Pastoris reached the highest level. In comparison, the alcohol oxidase activity was measured in an immobilized P. pastoris when entrapped in polyacrylamide gel beads. The alcohol oxidase activity of cells was induced by addition of 0.5% methanol as the carbon source. The cells were permeabilized by cetyltrimethylammonium bromide (CTAB) and immobilized. CTAB was also found to increase the gel permeability. Alcohol oxidase activity of immobilized cells was then quantitated by ABTS/POD spectrophotometric method at OD (420.) There was a 14% increase in alcohol oxidase activity in immobilized cells as compared with free cells. By addition of 2-butanol as a substrate, the relative activity of alcohol oxidase was significantly higher as compared with other substrates added to the reaction media. CONCLUSION: Immobilization of cells could eliminate lengthy and expensive procedures of enzyme separation and purification, protect and stabilize enzyme activity, and perform easy separation of the enzyme from the reaction media.